Pengenalan Mufradat Anggota Tubuh terhadap Anak Usia Dini - Vaesol Wahyu Eka Irawan (MOMENTUM : Jurnal Sosial dan Keagamaan, 2023)
Early childhood generally follows ages that are in the age range of 0-6 years. The development of children between 0 and 6 occurs very rapidly. Early childhood development is so rapid termed the golden age, the age at which human development occurs very rapidly before 7 years. Every human being experiences an early age that occurs once in a phase of life, no human being experiences an early age phase more than once, therefore early age should not be wasted. The purpose of this study is to describe the concepts, strategies, and media of introducing Arabic mufradat limbs to early childhood. The method used is qualitative with the type of literature research. The results of the study are as follows: The introduction of limb mufradat to early childhood aims to train and develop early cognitive competence, in addition to carrying out Islamic teachings, namely equipping early childhood to master basic Arabic. Mastery of Arabic is closely related to understanding the source of Islamic teachings. The source of Islamic teachings is the Qur'an and hadith. The Prophet (peace be upon him) once threatened explicitly that whoever interprets the Quran without knowledge then hell becomes his place. Introduction to Arabic mufradat of the limbs can be done with various strategies, methods, and learning media. Looking at early childhood development, a more appropriate medium is audio-visual media. Train early childhood to hear as well as see.